Benefits of energetic ion bombardment for tailoring stress and microstructural evolution during growth of Cu thin films. (December 2017) - Cemin, Felipe; Abadias, Gregory; Minea, Tiberiu; Furgeaud, Clarisse; Brisset, François; Solas, Denis; Lundin, Daniel
Abstract: We have studied the development of intrinsic stress and microstructure of copper (Cu) films deposited under energetic ion bombardment. Stress evolution during growth of ∼150 nm thick Cu films on Si(001) substrates has been investigated by in situ measurements in a high power impulse magnetron sputtering (HiPIMS) process for different substrate bias voltages (from 0 to −160 V) and benchmarked with conventional direct current magnetron sputtering (DCMS). The microstructure and crystal orientation of the studied films have been examined by various ex situ methods. For HiPIMS, we found that the substrate bias voltage (energy of Cu ions) strongly affects the film continuity during the early growth stages and the compressive stress developed during the post-coalescence stage. Contrarily to common expectations, the stress magnitude can be significantly reduced despite the energy increase of the bombarding particles when using HiPIMS. These results are discussed based on a recent kinetic model taking into account the grain size-dependent defect incorporation due to energetic particle bombardment. Reversible stress relaxations are observed upon growth interrupts, with characteristic time constants of tens of seconds, which suggests that the stress and microstructure development are mainly mediated by surface diffusion processes. In addition, polycrystalline films (111)-textured are obtained for negative bias voltages from 0 to −100 V, while for even higher negative bias voltages (up to −160 V), epitaxial growth of Cu(001) is achieved. For the DCMS samples, there is no significant change in film continuity and crystal orientation when varying the bias voltage. Graphical abstract: Image 1